2016
DOI: 10.1021/acs.energyfuels.6b01122
|View full text |Cite
|
Sign up to set email alerts
|

Shock Tube Study of Ignition Delay Characteristics of n-Nonane and n-Undecane in Argon

Abstract: Ignition delay times of n-nonane and n-undecane in 4% oxygen/argon have been measured behind reflected shock waves in a heated shock tube at temperatures of 1168−1600 K, pressures of 2, 10, and 20 atm, and equivalence ratios of 0.5, 1.0, and 2.0. Ignition delay times are determined by using CH* emission and pressure signals monitored at the sidewall. Results show that ignition delay times of two fuels decrease as the temperature or pressure increases, and a decrease in equivalence ratio results in a shorter ig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The present status on modeling and experimental studies on n-hexane, n-nonane and n-dodecane is summarized in Table 1. The ignition delay times of the above three hydrocarbons are well investigated and investigations are available for atmospheric to high pressures (20 -60 atm) in the temperature range of 700 -1600 K [28][29][30][31][32][33][34][35][36][37]. The characteristic burning velocities are studied mostly at atmospheric conditions [38][39][40] except for n-hexane (2, 5, and 10 atm) [41].…”
Section: Current Status On Larger Hydrocarbons Kineticsmentioning
confidence: 99%
“…The present status on modeling and experimental studies on n-hexane, n-nonane and n-dodecane is summarized in Table 1. The ignition delay times of the above three hydrocarbons are well investigated and investigations are available for atmospheric to high pressures (20 -60 atm) in the temperature range of 700 -1600 K [28][29][30][31][32][33][34][35][36][37]. The characteristic burning velocities are studied mostly at atmospheric conditions [38][39][40] except for n-hexane (2, 5, and 10 atm) [41].…”
Section: Current Status On Larger Hydrocarbons Kineticsmentioning
confidence: 99%
“…Compared with other MIs, the solubility of CBHPG in hydrocarbon fuels is impressive. n -Undecane, a main component of RP-3, was chosen to be the model fuel . The aggregate size of 0.20 wt % CBHPG in n -undecane at 25 °C is displayed in Figure e.…”
Section: Resultsmentioning
confidence: 99%
“…n-Undecane, a main component of RP-3, was chosen to be the model fuel. 49 The aggregate size of 0.20 wt % CBHPG in n-undecane at 25 °C is displayed in Figure 3e. It is found that the dissolved particle size of CBHPG in n-undecane increases with molecular weight, but all the particle sizes are below 8 nm.…”
Section: Characterization Of Hpg and Cbhpgmentioning
confidence: 99%
“…The detailed description of the existing experimental data on n -nonane combustion is shown in Table . , Although establishing a comprehensive n -nonane kinetic mechanism to describe its oxidation under a wide range of experimental conditions is important because of the complexity of large hydrocarbon fuels, the kinetic models currently used to describe n -nonane combustion are extremely rare, and are primarily acquired by manual construction. Among them, Westbrook et al developed a kinetic model (LLNL model) for describing the pyrolysis and oxidation of linear alkanes (from n -octane to n -hexadecane) over a wide temperature range; Wang et al developed a kinetic model (JetSurf 2.0 model) for the high-temperature oxidation of linear alkanes; cyclohexane; and methyl, ethyl, n -propyl, and n -butyl cyclohexanes.…”
Section: Introductionmentioning
confidence: 99%